Synthesis and Tautomerism of Substituted Pyrazolo[4, 3‐c]pyrazoles. Issue 30 (10th September 2013) - Kadam, Shivaji S.; Maier, Lukáš; Kostakis, Ioannis; Pouli, Nicole; Toušek, Jaromír; Nečas, Marek; Marakos, Panagiotis; Marek, Radek
Abstract: Fused five‐membered nitrogen heterocycles comprise a very important group of compounds frequently utilized in pharmaceutical applications. In this study, we report the first systematic synthesis of substituted pyrazolo[4, 3‐ c ]pyrazoles and three regioisomers of their N ‐methyl derivatives. All compounds were fully characterized by NMR spectroscopy in solution and selected compounds also were studied by X‐ray diffraction in the solid state. 1 H, 13 C, and 15 N NMR spectroscopic data for all isomers were interpreted by DFT calculations of nuclear shielding constants and indirect spin–spin coupling constants. The N ‐methyl isomers were used in the following steps as model compounds to investigate a potential N 1‐H/ N 4‐H, N 2‐H/ N 4‐H, and N 1‐H/ N 5‐H tautomerism of 3, 6‐substituted pyrazolo[4, 3‐ c ]pyrazoles by using low‐temperature NMR spectroscopy. All bases were shown to occur predominantly in the N 1‐H/ N 4‐H tautomeric form and the structure of minor form was governed by the substituents at positions 3 and 6. Stabilities of individual tautomeric forms are calculated by DFT methods and discussed. A relationship between the tautomeric populations and the ratios among N ‐methyl isomers obtained upon methylation of selected bases in solution are investigated. Abstract : The stability of various tautomeric forms of substituted pyrazolo[4, 3‐ c ]pyrazoles characterized by low‐temperature NMR spectroscopy can be qualitatively explained by electronic and steric effects of substituents in positions 3 and 6 in individual tautomers, as revealed by the DFT calculations.